2022
DOI: 10.3390/resources11080070
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in a Populated Coastal Zone and Its Influence by Oil Wells in Santa Elena, Ecuador

Abstract: The oil industry requires studies of the possible impacts and risks that exploration, exploitation, and industrialization can cause to the environment and communities. The main objective of this study was to assess the vulnerability caused by oil wells of the Salinas and La Libertad cantons in Ecuador by proposing a multi-criteria spatial analysis methodology that would aid in land-use planning and management. The proposed methodology relates the variables of distance, identification of gas emission from oil w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…Different geomatic tools, such as geographic information systems (GIS), are used in agricultural management, which analyze large amounts of spatial data on various topics [5,6]. For example, with other technological tools, GIS analyses the space-time of land use and land cover by agricultural activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Different geomatic tools, such as geographic information systems (GIS), are used in agricultural management, which analyze large amounts of spatial data on various topics [5,6]. For example, with other technological tools, GIS analyses the space-time of land use and land cover by agricultural activity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there is an increasing need for monitoring the shoreline position in order to track climate change-induced sea-level rises (SLR). Various studies have shown that satellite image analysis is a potentially powerful tool for monitoring coastal shoreline positions [1][2][3][4] as well as shoreline management strategies [5][6][7][8]. Shoreline position information is also crucial for coastal scientists and modellers, who need it to understand sediment transport and assess sediment budgets [9,10], predict the rates of coastal land loss or gain over time [11][12][13][14] and provide measures for assessing coastal vulnerability [7,8,15].…”
Section: Introductionmentioning
confidence: 99%
“…Oil exploration in Ecuador began in the coastal region, with the discovery of large oil reserves, proven by drilling the exploratory well Ancón-1 in 1911. It would be the beginning of oil exploitation in Ecuador [2]. In the 1940s, Shell explored the eastern basin and drilled several wells.…”
Section: Introduction 1formulation Of the Problemmentioning
confidence: 99%